Tectona grandis Linn. : ANTIDIABETIC ACTIVITY OF THE FRACTIONS USING AN IN VIVO APPROACH - Nurramadhani ASida; Rifa’atul Mahmudah; Nita Trinovitasari; Nada Shofa; Parawansah; Nuralifah; Abd Rafid; Risma (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
The exploration of Tectona grandis Linn. from Indonesia, especially its use as an anti-diabetes agent is still quite limited. This study aims to determine the antidiabetic activity of the fractions from Tectona grandis Linn. leaves in male Rattus norvegicus. The animal blood glucose level was measured first as T0, then the animals were injected with streptozotocin (STZ) 40 mg/Kg BW to induce diabetes mellitus (DM), and then the blood was collected to determine the blood glucose level (T1). The animal was divided into six groups, namely normal group (NC) without treatment, positive control (K+) (DM+glibenclamide 5 mg), negative control (K-) (DM+NaCMC 0.5%), fractions group (DM+nHexane fraction (P1), DM+chloroform fraction (P2), and DM+ethyl acetate fraction (P3), each dose 300 mg/kg BW). The duration of treatment was 7 days, and at the end of treatment, the blood glucose levels were determined. The T0, T1, and T2 are analyzed using One-Way ANOVA and post-hoc LSD. The results obtained that the K+, P3, P2, and P1 groups were able to reduce the animals' blood glucose levels significantly (p<0.05), with the blood glucose levels are 97.01; 110.96; 129.38; and 111.46 mg/dL, respectively. The percentage of reduction in blood glucose level shows that the K+ group has the highest percentage at 66.8%, followed by the P3 group at 64.0%. The n-hexane, chloroform, and ethyl acetate fractions showed similar effectiveness to glibenclamide in reducing blood glucose levels statistically (p>0.05). Consequently, Tectona grandis Linn ...